2006
DOI: 10.1111/j.1365-2672.2006.02835.x
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of Lactobacillus plantarum 423 and Lactobacillus salivarius 241 to the intestinal tract of piglets, as recorded with fluorescent in situ hybridization (FISH), and production of plantaricin 423 by cells colonized to the ileum

Abstract: Keywords bacteriocin production, fluorescent in situ hybridization, intestinal adhesion, lactic acid bacteria. AbstractAims: To determine which intestinal section of pre and postweaned piglets are colonized by Lactobacillus plantarum 423 and Lactobacillus salivarius 241, and follow production of plantaricin 423 in a gastro-intestinal model. Methods and Results: Lactobacillus plantarum 423 and Lact. salivarius 241, single or in combination, were administered to 1-, 14-and 28-day-old (postweaned) piglets. Accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 66 publications
(105 reference statements)
2
20
0
2
Order By: Relevance
“…Previous studies found L. plantarum to predominantly persist in the cecum and colon (5,57). In another study, L. plantarum 423 was reported to adhere to mucus isolated from the ileum and cecum of piglets (58). The CFU counts confirmed that the cecum and colon were the major sites of L. plantarum 423 and E. mundtii ST4SA colonization (Fig.…”
Section: Discussionsupporting
confidence: 65%
“…Previous studies found L. plantarum to predominantly persist in the cecum and colon (5,57). In another study, L. plantarum 423 was reported to adhere to mucus isolated from the ileum and cecum of piglets (58). The CFU counts confirmed that the cecum and colon were the major sites of L. plantarum 423 and E. mundtii ST4SA colonization (Fig.…”
Section: Discussionsupporting
confidence: 65%
“…Esto les permite pasar a través del tracto gastrointestinal sin sufrir alteraciones en su comportamiento fisiológico. Así, para que una cepa probiótica ejerza una óptima actividad es imprescindible que sea capaz de manifestar una actividad metabólica que le permita colonizar el intestino delgado; por lo que la tolerancia a bilis, es un criterio esencial de selección de bacterias lácticas (27).…”
Section: Discussionunclassified
“…Some investigators have investigated survival or activity of bacteriocin-producing strains but not bacteriocin stability in intestinal simulation studies (2,21). While Maré et al (15) confirmed plantaricin production in the ileal section of a gastrointestinal model, the solution used appeared to lack digestive enzymes. In the present study, RLSM was added (1:1) to simulated gastric juice or porcine gastric digesta (pH 2) and to simulated ileum juice or ileum digesta, and each of the mixtures was incubated at 37°C for 2 and 5 h, respectively.…”
mentioning
confidence: 99%